Utilizing Real – Time Face Recognition Based Bio-Metric System for Online Transaction - A. Dhivya,; K. Aashika,; S. Pavitha,; G. Varshini, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
A crucial component of contemporary banking is now online banking. Due to the present password- based authentication paradigm’s inadequacies in terms of efficiency and robust, as well as their suspectibility to automated attacks, several attempts are successful in gaining access to social network accounts. The easiest solution is to add more identifying features, like one-time PIN numbers that are created by the user’s own device(like a smart phone) or sent to them via SMS to the single factor(Password-based) authentication procedure. With the help of this technology, client’s identities may be instantly and conveniently verified. The goal of this project is to create an online banking system that authenticates customer’s using real-time facial recognition technology. The system will be made to offer a safe and convenient user interface that enables users to perform financial operation like bill payment, money transfers, and balance queries. A facial recognition algorithm, such Grassmann learning, which can record and evaluate customer’s facial traits in real time, will be included into the system. To confirm customer’s identification, the algorithm will match the customer’s facial traits with those in the bank’s database. The technology would give users a safe and convenient interface to conduct real-time banking transactions. Notifications about banking amount transactions are sent to the user in this suggested netbanking application.
Keywords: Online Banking; Face Recognition Technology; Grassmann Learning Algorithm; Real-Time Authentication; Funds Transfer; User-Friendly Interface; Security Notifications; Identity Verification